(untitled) (Journal of the College of Basic Education, 2025)
Our research entitled (The merit of the city of Mecca and its scholars over the scholars of Andalusia in receiving their religious knowledge through the books of biographies and translations until the end of the year (550 AH / 1155 AD) aims to identify the scientific journeys that the scholars of Andalusia followed through their travels to the East, especially to the city of Mecca, and because Mecca bears the qualities that God has honored it over all other places of knowledge and cooperation between the scholars of Mecca and those who traveled to them from Andalusia, Mecca was the owner of the merit in spreading knowledge in Andalusia through transferring their knowledge through the sheikhs and scholars of Andalusia who traveled to them. The researcher relied on the books of biographies and translations and the books of geographers in the research that was divided into four topics. The first topic was devoted to the status of Mecca in the Holy Quran and the Sunnah of the Prophet, the second topic Mecca in the books of geographers and its scientific and religious status in the souls of the people, the third topic scientific journeys, and the fourth topic scholars of Andalusia who traveled to Mecca..